Characteristics of Hydrological Variables of the Semenyih River Basin, Selangor, Malaysia - Barzani Gasim, Muhammad; Sulaiman, an Nor Azmin; Ismail Yaziz, Mohd.; Samsudin, bd. Rahim (Malaysian Journal of Science, 2005)
The Semenyih River Basin has 36 sub-basins; consisting of 25 medium sub-catchments, which cover a total surface area of 230.94 kmÃ‚Â², and II small sub-catchments with a total area of 35.66 kmÃ‚Â² including the Semenyih Dam. Field measurements of Semenyih River was carried out twice i.e. during dry (12/1998) and wet (03/1999) seasons, to determine the variation of the hydrological characteristics such as velocity, stream flow rate and runoff. The total length of the Semenyih River with respect to the water sampling stations (St.1-St.11) in the study area is 37km and is divided into three different zones based on the slope gradient percentage, namely the upper, the middle and the lower zones. Based on stream flow measurements at St.II, the Semenyih River has a total discharge of between 9.90 to 15.60 cumec or equal to 0.85x 10Ã¢ÂÂ¶mÃ‚Â³ to 1.30x 10Ã¢ÂÂ¶mÃ‚Â³ of potable water daily. Demand of water (0.53 x 10Ã¢ÂÂ¶ mÃ‚Â³/day) to fulfill the Sg. Semenyih Water Treatment Plant is more than enough until 2010. Abbrev: mÃ‚Â³=cubic meter; cumec=cubic meter/second; kmÃ‚Â²=square kilometer; sec= second